Análise econômica e de eficiência produtiva da produção industrial de frangos de corte e perspectivas de integração em Minas Gerais - Edgard Onoda Luiz Caldas (2018)
The success of the national poultry industry is based on the poultry integration system, however, it is possible to observe that integrating companies still use their own breeding equipment to supply their slaughterhouses. Therefore, this study aimed to verify, based on economic analysis and productive efficiency, which governance structure would be the most appropriate for the birds breeding and what is the interest level of rural producers in investing resources in the poultry integration system in Minas Gerais. Case studies were used as research methods to evaluate the activity in the creation centers of the integrating company and the integrated rural producers. The field research was carried out to collect primary data on costs, income and zootechnical indicators in 36 poultry production units belonging to an integrated company and five integrated rural producers, located in the Brazilian state of Minas Gerais. Data from 216 batches of broilers produced between August 2015 and August 2016 were used in economic analysis and evaluations of productive efficiency. It was verified that the breeding of poultry via hierarchical governance generated worse results than those acquired by the contractual relationship with rural integrated producers. Although the integrating company obtained operating income in male-only aviaries and with a negative pressure air conditioning system, in all the breeding units through hierarchical governance there was economic loss in the activity. The financial simulation indicated that the integrating company could save R$ 845,477.08 per year if it decided to produce broilers only by integration contracts. Overall, it was noticed a low productive efficiency in poultry breeding through hierarchical governance, due to technical and scale inefficiencies. Surveys of primary data were used to assess the level of interest of rural producers in investing resources in the poultry integration system in the Brazilian state of Minas Gerais. It was made the data collection through semi-structured interviews with ten rural producers integrated into the agroindustrial system of broilers. Despite troubles, disadvantages and restrictions regarding the integration system have been identified, 90% of the integrated rural producers expressed interest in investing in new facilities resources. Resulting, thus, positive the conditions for expansion of the poultry activity through integration contracts